2022
DOI: 10.1298/ptr.e10205
|View full text |Cite
|
Sign up to set email alerts
|

Initiating Mobilization Is Not Associated with Symptomatic Cerebral Vasospasm in Patients with Aneurysmal Subarachnoid Hemorrhage: A Retrospective Multicenter Case-control Study

Abstract: The study aim was to investigate the association between initiating mobilization within 7 days after onset and symptomatic cerebral vasospasm (SCV) in patients with aneurysmal subarachnoid hemorrhage (aSAH). Methods: This was a retrospective multicenter case-control study in Japan. Patients with a diagnosis of aSAH who underwent physical therapy with/without occupational therapy were included and categorized into 2 groups according to the presence or absence of SCV. Initiating mobilization was defined as sitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
(57 reference statements)
2
4
0
Order By: Relevance
“…In a randomized controlled study, cerebral ischemia and motor paralysis were increased when early mobilization was initiated within 2-5 days of onset (47). However, other studies have reported a decrease in SCV or no association with early mobilization (30,45). In the present study, the incidence of SCV was lower in the early mobilization group (4.1%) than in the delayed mobilization group (22.1%), which is consistent with previous studies (30,45).…”
Section: Several Factors May Explain the Association Between Walking ...supporting
confidence: 89%
See 2 more Smart Citations
“…In a randomized controlled study, cerebral ischemia and motor paralysis were increased when early mobilization was initiated within 2-5 days of onset (47). However, other studies have reported a decrease in SCV or no association with early mobilization (30,45). In the present study, the incidence of SCV was lower in the early mobilization group (4.1%) than in the delayed mobilization group (22.1%), which is consistent with previous studies (30,45).…”
Section: Several Factors May Explain the Association Between Walking ...supporting
confidence: 89%
“…However, other studies have reported a decrease in SCV or no association with early mobilization (30,45). In the present study, the incidence of SCV was lower in the early mobilization group (4.1%) than in the delayed mobilization group (22.1%), which is consistent with previous studies (30,45). Furthermore, the early mobilization group had lower rates of higher brain dysfunction and lower limb paralysis, potentially because of fewer instances of SCV.…”
Section: Several Factors May Explain the Association Between Walking ...supporting
confidence: 89%
See 1 more Smart Citation
“…After duplicate removal (n = 807), 1927 records were screened and 398 were then assessed for eligibility through full-text screening. Finally, 11 studies that met the inclusion and exclusion criteria and reported on 1460 patients were identified and included in the qualitative synthesis, [17][18][19][20][21][22][23][24][25][26][27] with 10 studies analyzing 1292 patients available for inclusion in the quantitative synthesis. [17][18][19][21][22][23][24][25][26][27] The two publications by Karic et al from 2016 and 2017 reported almost exactly the same cohort; quantitative data appropriate for this analysis were, however, exclusively reported in the 2017 publication.…”
Section: Literature Searchmentioning
confidence: 99%
“…Finally, 11 studies that met the inclusion and exclusion criteria and reported on 1460 patients were identified and included in the qualitative synthesis, [17][18][19][20][21][22][23][24][25][26][27] with 10 studies analyzing 1292 patients available for inclusion in the quantitative synthesis. [17][18][19][21][22][23][24][25][26][27] The two publications by Karic et al from 2016 and 2017 reported almost exactly the same cohort; quantitative data appropriate for this analysis were, however, exclusively reported in the 2017 publication. 20,22 Sufficient data were available to perform a meta-analysis of mRS score at discharge, 30-day mortality, clinical and radiological vasospasm, length of stay, hydrocephalus, EVD and LD device placement, ventriculoperitoneal shunting, DVT, and pneumonia.…”
Section: Literature Searchmentioning
confidence: 99%